Photophysical and Photochemical Properties of Naturally Occurring normelinonine F and Melinonine F Alkaloids and Structurally Related N(2)‐ and/or N(9)‐methyl‐β‐carboline Derivatives. (20th September 2017) - Rasse‐Suriani, Federico A. O.; García‐Einschlag, Fernando S.; Rafti, Matías; Schmidt De León, Tobías; David Gara, Pedro M.; Erra‐Balsells, Rosa; Cabrerizo, Franco M.
Abstract: In the present work, we have synthesized and fully characterized the photophysical and photochemical properties of a selected group of N‐methyl‐ β ‐carboline derivatives (9‐methyl‐ β ‐carbolines and iodine salts of 2‐methyl‐ and 2, 9‐dimethyl‐ β ‐carbolinium) in aqueous solutions, in the pH range 4.0–14.5. Moreover, despite the quite extensive studies reported in the literature regarding the overall photophysical behavior of N‐unsubstituted β Cs, this work constitutes the first full and unambiguous characterization of anionic species of N‐unsubstituted β Cs ( nor harmane, harmane and harmine), present in aqueous solution under highly alkaline conditions (pH > 13.0). Acid dissociation constants ( K a ), thermal stabilities, room temperature UV–visible absorption and fluorescence emission and excitation spectra, fluorescence quantum yields ( Ф F ) and fluorescence lifetimes ( τ F ), as well as quantum yields of singlet oxygen production ( Ф Δ ) have been measured for all the studied compounds. Furthermore, for the first time to our knowledge, chemometric techniques (MCR‐ALS and PARAFAC) were applied on these systems, providing relevant information about the equilibria and species involved. The impact of all the foregoing observations on the biological role, as well as the potential biotechnological applications of these compounds, is discussed. Abstract : Photophysical characterization of different acid‐base species of nor melinonine F and melinonine F alkaloids and other closely related 2‐, 9‐, and 2, 9‐substituted‐ β ‐carbolines in aqueous solution, in the pH range 4.0–14.5.